Household Fuel Transition and Determinants of Firewood Demand in Nepal - Sharma, Bishnu Prasad (Economic Journal of Development Issues, 2019)
There is an emerging challenge of providing cleaner fuel to household to avoid various health risks arising from the use of traditional non-cleaner fuel and to cope with the challenges created by climate change. The energy transition theories explain how societies switch from traditional to more advanced fuels that are cleaner and efficient. The paper examines the state of fuel transition and determinants of firewood dependence in Nepal. This paper uses data collected in 2013 from three different ecological zones through household surveys. The findings revealed that biomass fuel particularly firewood is the dominant form of fuel used for household cooking with 84 percent dependence followed by LPG 9 percent, biogas 6 percent and electricity around 1 percent. The findings revealed that energy security through energy stacking is a dominant phenomenon. Presence of alternative fuel that are cleaner and convenient and ecological factors are major determinants of household firewood demand followed by literacy status, landholding size, household size, presence of large ruminant. Firewood consumption had negative relation with its price but the relation was not economically significant. In contrast to the study hypotheses, household income and remittance were not determining factors. In view of wider coverage of electricity, there is prospect for shifting to renewable fuel sources through appropriate pricing and technological improvement policies.